2006
DOI: 10.1080/09546630600552216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new moisturizer (Exomega milk®) in children with atopic dermatitis

Abstract: The milk emollient studied was found to provide an interesting auxiliary treatment in childhood atopic dermatitis since it gave positive results, in particular on xerosis and pruritus, as well as an improvement of the quality of life of the children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 6 publications
1
59
0
Order By: Relevance
“…The smaller trial by Giordano-Labadie and colleagues 192 found no significant difference between the groups in the severity of eczema measured using SCORAD scores after 28 or 56 days of treatment. The authors report a significant reduction in the emollient group and the control group for both xerosis (-35.9% vs. -68.6%; p = 0.01) and pruritus (-41.6% vs. -65.7%; p = 0.01) after 2 months of treatment, although these were not prespecified outcomes.…”
Section: Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The smaller trial by Giordano-Labadie and colleagues 192 found no significant difference between the groups in the severity of eczema measured using SCORAD scores after 28 or 56 days of treatment. The authors report a significant reduction in the emollient group and the control group for both xerosis (-35.9% vs. -68.6%; p = 0.01) and pruritus (-41.6% vs. -65.7%; p = 0.01) after 2 months of treatment, although these were not prespecified outcomes.…”
Section: Benefitsmentioning
confidence: 99%
“…Most of the 15 new trials 123,126,[190][191][192][193][194][195][196][197][198][199][200][201][202] looking at emollients reported after 2000 compared twice-daily treatment with an emollient (often applied concurrently with topical corticosteroid treatment) with treatment with topical corticosteroids alone, other emollients or, in one case, no treatment. Most trials had a treatment length of around 4-6 weeks and none of the trials gave treatment for > 2 months.…”
Section: Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 67 articles satisfied our criteria [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73]. Sixteen concerned atopic dermatitis [7, 13, 14, 18,20,21,22, 26, 29, 31, 42, 46, 56, 66, 67, 70], 1 chronic eczema of the hands [9], 25 psoriasis [10, 17, 27, 30, 33,35,36,37,38,39,...…”
Section: Resultsmentioning
confidence: 99%
“…[4,5] A study examining the role of ceramide-containing emollients showed some improvements; however, the results were not properly evaluated. The latest addition to these products contain, in addition to ceramides, filaggrin breakdown products to replace the 'missing' molecules in the atopic skin.…”
Section: Emollientsmentioning
confidence: 99%